2011
DOI: 10.1080/1573062x.2010.546862
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of local water supply systems in suburban Belgrade

Abstract: In suburban Belgrade, there are some 200 local water supply systems which are not connected to either the Belgrade Water Supply System or to supply systems operated by municipal utilities. The small systems in Belgrade suburbs are either operated by local municipality (local government) or even by the group of local citizens who have neither technical capability nor financial resources to do it properly. Roughly 200,000 of Belgrade's inhabitants obtain their drinking water from these water supply systems. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
(9 reference statements)
0
3
0
1
Order By: Relevance
“…The results of a study conducted in suburban Belgrade, which included 200 local water supply systems, showed that 7% of the samples exhibited elevated nitrite levels. Additionally, out of the 38 water samples collected at 25 sites, 39.5% did not comply with the limit values for one or more of the tested elements (ammonium, nitrites, nitrates, and iron) [22], as the limited values were exceeded.…”
Section: Discussionmentioning
confidence: 98%
“…The results of a study conducted in suburban Belgrade, which included 200 local water supply systems, showed that 7% of the samples exhibited elevated nitrite levels. Additionally, out of the 38 water samples collected at 25 sites, 39.5% did not comply with the limit values for one or more of the tested elements (ammonium, nitrites, nitrates, and iron) [22], as the limited values were exceeded.…”
Section: Discussionmentioning
confidence: 98%
“…The risks to human health from chronic arsenic exposure are not all reversible once exposure has ended (note that there are many ways to define and analyze risks in water supply; see Sadiq et al (2007), Lindhe et al (2011) and Petkovic et al (2011) for some examples). Latent health effects, many fatal, may take decades to appear.…”
Section: Introductionmentioning
confidence: 99%
“…China is one of the thirteen countries that lack per capita water resources. Regional water shortages will not only lead to pressure for water use, but will also negatively affect the water supply sector, resulting in a deterioration of the quality of the water supplied to the residents (Sadiq et al, 2007;Petkovic et al, 2011;Lindhe et al, 2012;Boryczko & Tchórzewska-Cieślak, 2014). In addition, China is a major exporter according to figures released by the General Administration of Customs.…”
Section: Introductionmentioning
confidence: 99%